Mechanical properties and repairing mechanism of recycled cement stabilized macadam for road base based on microbial induced carbonate precipitation technology - Xiao Qin; Yongkang Lin; Sen Chen; Xiaolong Sun; Xinhua Yang; Qingjian Huang (Case Studies in Construction Materials, 2024)
The utilization of recycled coarse aggregate derived from construction and demolition waste (CDW) in the construction of road cement stabilized macadam base could effectively alleviate the shortage of natural sand and aggregate resources. To explore the repairing effect of microbial induced carbonate precipitation (MICP) on recycled cement stabilized macadam (RCSM), the physical, mechanical, and microscopic properties of recycled concrete aggregate under different precipitation precursor concentrations were researched in this paper. The mechanical properties of RCSM with varying contents of recycled concrete aggregate were analyzed before and after repairing. Based on scanning electron microscopy (SEM) and mercury intrusion porosimeter (MIP) tests, the microstructure and pore structure parameters of recycled concrete aggregate were explored, and the repair mechanism of MICP on RCSM was revealed via the performance analysis of recycled concrete aggregate and RCSM. The results show that MICP could effectively reduce the water absorption of recycled concrete aggregates, while simultaneously enhancing its apparent density and crushing resistance. In a certain range, the higher the concentration of the precipitation precursor, the better the repairing effect on the performances of recycled concrete aggregates. However, while the concentration of urea or calcium source concentration exceeding 1.0 mol/L, the activity of urease would start to be inhibited. The unconfined compressive strength of RCSM after MICP repairing could be increased by 22.7 % with a maximum extent compared with that before repair, while the maximum increase of indirect tension strength and flexural tensile strength was 15 % and 8.2 %, respectively. The biological CaCO3 generated by MICP reaction could fill the micro-cracks and pores of the recycled concrete aggregate efficaciously. Besides, it could also optimize the pore parameters and pore size distribution parameters, and enhance the adhesive strength of interfacial transition zone (ITZ) between cement and recycled concrete aggregates, which could improve the mechanical properties of RCSM.